The Good, the Not So Good and the Ugly: Gender Equality, Equal Pay and Austerity in English Local Government. (August 2018) - Conley, Hazel; Page, Margaret
Drawing on theories of responsive and reflexive legislation and gender mainstreaming, this article examines the implementation of the gender equality duty and the Single Status Agreement in five English local authorities between 2008 and 2010. Both of these initiatives coincided with the global financial crisis. The data highlights how organizational restructuring following budget cuts resulted in the separation of these two important initiatives between equality and human resource management teams, preventing the duty from reaching the high expectations of the Equal Opportunities Commission and the Women and Work Commission. The reliance on equal pay legislation and the failure to use the gender equality duty missed an opportunity to move away from adversarial forms of legislation and towards more responsive forms of regulation of pay equality.